Efforts to Prevent Stunting in Early Childhood with BANTING (Stunting-Free) MPASI in Petiken Village, Driyorejo District, Gresik Regency - Rahmawati, Aisah; Luqyana, Dhia; Indah, Fransiska (Journal of Health Community Service, 2023)
Stunting is a chronic nutritional problem that has a serious impact on children's growth and development. This counseling aimed to analyze the influence of the program on Complementary Foods for Breastfeeding (MPASI) on public knowledge about stunting. This counseling was carried out in Petiken Village, Driyorejo District, Gresik Regency. The research method used is an observational method with a pretest-posttest approach. The results of the data analysis show that the extension program has a significant positive impact in increasing public knowledge about stunting and the provision of complementary foods. Posttest data is normally distributed, while pretest data is not normally distributed. The recommendation of this study is the need to develop a broader and integrated extension program with existing health resources.